Fotografias do senado na Wikipédia: circulação de imagens e construção coletiva de memória - Amaral, Tadeu Sposito do (2019)
Brazilian Federal Senate promotes the photographic coverage of legislative activity and events of institutional interest, uses these photos in its communication system and publishes them in image bank, so that the material can be used freely. Some of this material is used to illustrate Wikipedia articles, in a phenomenon of appropriation and resignification. These photographs contribute to the process of building public collective memory about the Senate itself, the Parliament and even the Brazilian nation. This study deals with this dynamics of reuse and the decentralized process of memory construction, once concentrated in the hands of the State itself, scenario that changes with the advent and popularization of digital technologies. With the perspective that this memory is one of the elements of the exercise of citizenship, this research studies photos not looking at them, but at the context: where they come from, where they were originally published, and where they where used. To do so, all the images produced by the Senate News Agency's Photography Service published on Wikipedia until October 2019 were identified, so that the object of research could be reached: the Senate's descriptions of the photographs and the articles in the which were used. The methodology adopted is based on Bardin’s content analysis. The texts accompanying the 1219 images were analyzed, as well as the contents of the 2112 Wikipedia. entries that displayed them, distributed in 90 versions of the encyclopedia. It was found that this material has great relevance in the composition of articles that relate to the Senate and the Brazilian State, and also composes pages that have no relation to the institution, thanks to the characteristics of images and the way content is produced and used on the internet.